A Hybrid Simulation of Converter-Interfaced Generation as the Part of a Large-Scale Power System Model; International Journal of Engineering and Technology Innovation (IJETI); Vol. 11, iss. 4 - Razzhivin I. A. Igor Andreevich; Askarov A. B. Alisher Bakhramzhonovich; Rudnik V. E. Vladimir Evgenevich; Suvorov A. A. Aleksey Aleksandrovich (2021, 2021)
Title screen